Using language for social interaction: Communication mechanisms promote recovery from chronic non-fluent aphasia. (December 2016) - Stahl, Benjamin; Mohr, Bettina; Dreyer, Felix R.; Lucchese, Guglielmo; Pulvermüller, Friedemann
Abstract: Introduction: Clinical research highlights the importance of massed practice in the rehabilitation of chronic post-stroke aphasia. However, while necessary, massed practice may not be sufficient for ensuring progress in speech-language therapy. Motivated by recent advances in neuroscience, it has been claimed that using language as a tool for communication and social interaction leads to synergistic effects in left perisylvian eloquent areas. Here, we conducted a crossover randomized controlled trial to determine the influence of communicative language function on the outcome of intensive aphasia therapy. Methods: Eighteen individuals with left-hemisphere lesions and chronic non-fluent aphasia each received two types of training in counterbalanced order: (i) Intensive Language-Action Therapy (ILAT, an extended form of Constraint-Induced Aphasia Therapy) embedding verbal utterances in the context of communication and social interaction, and (ii) Naming Therapy focusing on speech production per se . Both types of training were delivered with the same high intensity (3.5 h per session) and duration (six consecutive working days), with therapy materials and number of utterances matched between treatment groups. Results: A standardized aphasia test battery revealed significantly improved language performance with ILAT, independent of when this method was administered. In contrast, Naming Therapy tended to benefit language performance only when given at the onset of the treatment, but not when applied after previous intensive training. Conclusions: The current results challenge the notion that massed practice alone promotes recovery from chronic post-stroke aphasia. Instead, our results demonstrate that using language for communication and social interaction increases the efficacy of intensive aphasia therapy.